2013
DOI: 10.1309/ajcpuy0zmg3vtlfg
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Myelomonocytic Leukemia Monocytes Uniformly Display a Population of Monocytes With CD11c Underexpression

Abstract: A distinct heterogeneous population of monocytic cells with underexpression of CD11c was identified in all these cases. CD11c underexpression was independent of other aberrancies, including HLA-DR underexpression (n = 14), aberrant CD56 expression (n = 11), and underexpression of CD33, CD38, and CD14 (n = 6, 5, and 5, respectively), supporting the utility of CD11c expression status on monocytes in establishing a CMML diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…In CMML, monocytes, granulocytes, and blasts exhibit aberrant antigen expression. (12)(13)(14)16,17) Similar abnormalities may be seen in a small subset of reactive monocytosis cases. (2) Most of the previous studies evaluating CMML have primarily used normal bone marrow for comparison.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…In CMML, monocytes, granulocytes, and blasts exhibit aberrant antigen expression. (12)(13)(14)16,17) Similar abnormalities may be seen in a small subset of reactive monocytosis cases. (2) Most of the previous studies evaluating CMML have primarily used normal bone marrow for comparison.…”
mentioning
confidence: 64%
“…Twelve of 34 (35%) and 16 of 34 (47%) CMML cases exhibited two or more phenotypic alterations in monocytes and in granulocytes, respectively (Table ). We found that CD56 expression was the most common aberrancy in CMML, which has been described in several studies . However, CD56 expression on monocytes is not specific for CMML as it can be present in reactive monocytes (inflammatory responses), post‐chemotherapy hematopoietic regeneration, Down syndrome, myeloproliferative disorders, and other myelodysplastic/myeloproliferative disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations